1989
DOI: 10.1007/bf03190113
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine pharmacokinetics and effect in the Type I diabetic rat model

Abstract: Recent clinical studies have demonstrated the potential benefit of the T-cell-specific immunosuppressant, cyclosporine, in the treatment of Type I insulin-dependent diabetes. In the present study, steady-state cyclosporine pharmacokinetics, fasting glucose and insulin levels and renal function were examined in stable insulin-dependent diabetic rats and compared to non-diabetic rats. Mean creatinine clearance 30 days following diabetes induction was not significantly different from saline controls. Cyclosporine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Our previous study showed that the exposure to baicalin was increased after oral administration in diabetic rats but decreased after intravenous administration . Another report demonstrated that cyclosporine in diabetic rats after intravenous administration was significantly lower than that in control rats (Brunner et al, 1989). In contrast, the AUC of cyclosporine in diabetic rats after an oral dose was approximately 65% greater than that in control rats (Ogata et al, 1996).…”
Section: Discussionmentioning
confidence: 97%
“…Our previous study showed that the exposure to baicalin was increased after oral administration in diabetic rats but decreased after intravenous administration . Another report demonstrated that cyclosporine in diabetic rats after intravenous administration was significantly lower than that in control rats (Brunner et al, 1989). In contrast, the AUC of cyclosporine in diabetic rats after an oral dose was approximately 65% greater than that in control rats (Ogata et al, 1996).…”
Section: Discussionmentioning
confidence: 97%
“…[155,156] After the intravenous administration of 5 mg/kg per day ciclosporin for 13 days to male CD DMIS rats on the 35th day, their AUC values became significantly smaller (by 31.9%) than that of the controls. [157] This could possibly have been due to the significantly faster in-vitro CL int for the disappearance of ciclosporin (not measured) in the DMIS rats. This was because ciclosporin is a drug with a low hepatic extraction ratio drug in rats (its 'indirect' hepatic first-pass effect was found to be 14.7%).…”
Section: Diclofenacmentioning
confidence: 98%
“…This was because ciclosporin is a drug with a low hepatic extraction ratio drug in rats (its 'indirect' hepatic first-pass effect was found to be 14.7%). [157] The faster hepatic CL int could have been due to the increase in the protein expression or mRNA levels of hepatic CYP3A1, 3A2, and 3A1/2 in the DMIS rats (Table 1). [16,17,21] However, different results have been reported.…”
Section: Diclofenacmentioning
confidence: 99%
See 1 more Smart Citation
“…Another example is cyclosporin A. Cyclosporin A is also a substrate of CYP3A, MRP2, P-gp, OATP1B1 and BCRP. Significantly increased systemic clearance of cyclosporin A in diabetic rats [77] should be attributed to the net effect of alterations in these transporters and CYP3A. Methotrexate transport in the liver is mediated by various transporters such as OATP1B1, MRP2, BCRP and OAT2.…”
mentioning
confidence: 99%